ANALYSIS OF IMPLEMENTATION OF LOCAL LABOR RECRUITMENT IN JOUMPA UNIT AS A FORM OF SOCIAL RESPONSIBILITY OF PT GAPURA ANGKASA BRANCH DENPASAR - Renaldi, I Putu Alit; Abiyasa, Agus Putu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
JOUMPA has the meaning "Your Journey Companion" which if translated into Indonesian means "Your Travel Companion", which is expected to be able to provide excellent service and convenience for airplane passengers while at the airport, through various services from pre journey, pre flight, post flight to post journey. JOUMPA (Your Journey Company) is a service owned by PT. Gapura Angkasa which has responsibilities as an air transportation operational support company and as the largest Ground Handling company in Indonesia. A VIP service that provides convenience services for airplane passengers at the airport through a variety of services provided. In providing good service, qualified human resources are needed to support the process of providing services. The author is interested in finding out how to implement the recruitment of workers in this joumpa, whether to use local workers so that this company is also responsible for its social environment.